TÜRK DİN MÛSİKÎSİ ÜSTÂDLARINDAN SEBİLCİ HÜSEYİN EFENDİ - POLATTEMİR, ALİ (Fırat Üniveristesi, 2014)
İslam Dinî, güzel sanatlarımızın her alanında olduğu gibi, büyük ve köklü bir yapıya sahip olan Mûsikîmiz üzerinde de etkisini yoğun bir şekilde hissettirmiştir. Bu etkiyle beraber birçok sanatkârımız, Türk Mûsikîsi içerisinde kendine has özelliklere sahip yeni türler ve bu türlerde eserler vücuda getirmişlerdir. Meydana getirilen bu eserler, Mûsikîmizin "Dinî" ve "Lâ-Dinî" olarak ikiye ayrılmasına vesile olmuştur. Lâ-Dinî Türk Mûsikîsi'nde olduğu gibi kendine has özellikleri olan Türk Din Mûsikîsi'nde de birçok sâzende, hânende ve bestekâr yetişmiş, bu Mûsikî türünü yaptıkları katkılarla zirveye ulaştırmışlardır. Söz konusu bu mûsikîşinaslardan biri de hiç şüphesiz, çalışmamıza konu olan Sebilci Hüseyin Efendi'dir. Çalışmamız bu değerli mûsikîşinasın hayatını, sanatçı kişiliğini, İlâhî Formunda bestelediği on tane eserinin tür ve biçim yönünden ele alınıp incelenmesini ve bu eserlerin müzikal analizlerini konu edinmiştir. Anahtar Kelimeler: Sebilci Hüseyin Efendi, Sâzende, Hânende Mersiyehân, Gazelhân, Türk Din Mûsikîsi.

İslam Religious,as in all every areas of our fine art, make feel its intensively effect on the Turkish Music which has a great and well established structure, too. With this effect, plenty of musicians have made new types which has specific characteistic in Turkish Music and new works in these types. These Works had caused to is divided two as Religious and Non-Religious of our Turkish Music. Like Non religious Music, plenty of Musicians who plays Turkish Instrument, singers and composers were trained in Turkish Religious Music which has specific characteristic, too. They provided this type of music to reach peak levels with their assistances. One of these assessment roll musicians is Sebilci Hüseyin Efendi who comes up for our work without a shadow of doubt. Our study have addressed this valuable Turkish Musician's life, artist personality, by examining ten works which he composed in hymn form with regard to type and form and of these Works musical analysis. Keyword: Sebilci Hüseyin Efendi, Musician who plays Turkish Instrument, Singer Of Turkish Music, Dirge Singer, Ghazal Singer, Turkish Religious Music.
Sebilci Huseyin Efendi who is one of the masters of the Turkish religious music
Keywords: Müzik